Retention mucocele on the lower lip associated with inadequate use of pacifier - Alves, Levy A. [UNESP]; Di Nicoló, Rebeca [UNESP]; Ramos, Carolina J. [UNESP]; Shintome, Luciana [UNESP]; Barbosa, Cristiani S. [UNESP] (My University, 2010)
Mucocele forms because of salivary gland mucous extravasation or retention and is usually related to trauma in the area of the lower lips. Ruptured ducts release the mucous that accumulates into adjacent tissues, leading to swelling. This report describes a large mucocele involving the lower lip, which was produced in a child by incorrect use of a pacifier. A few important concepts are discussed to help clinicians in the diagnosis and treatment of this pathology. © 2010 Dermatology Online Journal.
Keywords: case report; child; child care; clinical feature; disease association; epithelium hyperplasia; female; granulation tissue; histopathology; human; human tissue; hydrophobicity; lip disease; lip hemorrhage; lymphocytic infiltration; mouth edema; mucocele; oral biopsy; oral surgery; pacifier; preschool child; recurrent disease; tissue degeneration